The Effect of Periodontal Treatment on the Reactive Hyperemia Index. A 1-Year Follow-Up Pilot Study - Donders, H. C. M.; Veth, E. O.; Edens, M. A.; van ’t Hof, A. W. J.; de Lange, J.; Loos, B. G. (Frontiers in Cardiovascular Medicine, 2022)
ABSTRACT Background Periodontitis is a chronic multifactorial inflammatory disease of the supportive tissues of the teeth. In more recent years, remarkable epidemiological and pathophysiological associations between periodontitis and cardiovascular disease (CVD) have been presented. Whether or not treatment of periodontitis is valuable for primary or secondary prevention of cardiovascular disease, has not yet been fully established. In this practice-based pilot study we focused on primary prevention of cardiovascular disease, by investigating the effect of periodontal treatment on the earliest detectable stage of CVD; endothelial dysfunction. Methods Otherwise healthy periodontitis and non-periodontitis patients 45-70 years of age were included in the study. One year after completing periodontal (non-surgical and surgical) treatment of the periodontitis patients and one year after inclusion of the controls, all baseline measurements were repeated. Full-mouth examinations were performed by a periodontist to determine their Periodontal Inflamed Surface Area (PISA) score and other dental parameters. To assess the cardiovascular conditions, endothelial function through the reactive hyperemia index (RHI) assessed by the EndoPAT ™, and several physical and biochemical parameters were measured. Results 21 patients with diagnosed, untreated periodontitis and 21 patients without periodontitis were included in this follow-up study. After periodontal therapy in the periodontitis patients, the PISA reduced significantly. The RHI did not show a significant improvement after treatment of the periodontitis patients (-0.1 ± 0.8, p=0.524). Similarly, other secondary cardiovascular outcome measurements, hsCRP, total cholesterol, HDL cholesterol, triglycerides, HbA1c and systolic blood pressure did not improve significantly after periodontal treatment. Controls did not show any significant changes in the RHI, in other CVD parameters and in the PISA after one-year follow-up. Conclusions In this practice-based pilot study, periodontal treatment did not improve the endothelial function in otherwise healthy adults with periodontitis. Future studies are needed to be of larger size and could focus on periodontitis patients with co-morbidities to investigate whether periodontal treatment has secondary preventive effect on endothelial function and other CVD parameters.